APPLICATION OF THE ISTISHLAH CONCEPT IN THE FATWA INSTRUMENT REGARDINGSOCIAL SECURITY ADMINISTRATOR AGENCY (BPJS) PRODUCTS SYARIAH HEALTH - Taufik Hidayat (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study explores the concept of istishlah (seeking public interest) as a method used by the Indonesian Ulema Council (MUI) in formulating fatwas (Islamic legal rulings) to address contemporary issues. Focusing on MUI's fatwa regarding Sharia-compliant products from the Social Security Administering Body (BPJS Kesehatan Syariah), the research examines the position of istishlah within Islamic law, the criteria established by MUI for Sharia Health Social Security Agency (BPJS) products, and how the sharia label affects people's medical treatment preferences. The study employs library research and interviews with MUI Fatwa Commission members to analyze the application of istishlah in addressing the complexities of social security within an Islamic framework, aiming to promote public welfare in accordance with Sharia principles.